Techne as technology and Techne as Art: Heidegger’s phenomenological perspective - D. Rio Adiwijaya (Graduate School of Institut Seni Indonesia Yogyakarta, 2018)
We live in an age where our existence has been remarkably shaped by technology. However, as contemporary thinkers have elucidated, technology is not a mere sum of our tools. At a more profound level, technology forms an instrumental context that frames our relation to the world and to ourselves. Everything thereupon tends to appear merely as a means to an end. Countering the instrumentalistic tendencies of global technologization, this paper would like to ponder on the meaning of technology beyond mere tools. The core influence of this study is the thought of Martin Heidegger (18891976) which reveals that both technology and art stem from ancient techne, our basic way to reveal reality through embodied praxis. However, 2500 years of Western intellectual history has rendered the instrumental meaning of techne – that is, the way we understand technology today as practical utilization of science – becomes far more dominant than the artistic or poetic one. It is the aim of this literary study to elucidate Heidegger’s dense phenomenological inquiry which reveals the dual meaning of techne: techne as technology and techne as art. Recovery of the forgotten poetic meaning of techne is crucial to counter instrumentalism that pervades art in our techno-scientific age.